SIMULATION OF THE PROCESS OF RESEARCH COMPETENCIES FORMATION OF TECHNICAL UNIVERSITIES STUDENTS - GeorgiyM. Maksimovich Il'mushkin; Aleksey G. Il'mushkin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The work is devoted to the modeling of the system of development of research competencies of students of technical universities. In the developed model its main components are highlighted. In particular, the fundamental target of the development of scientific-research work of students is identified, the main principles of its organization are singled out. The system’s strategic principle is the principle of fundamentality and professional orientation. This proves the key role of the principle of continuity. The main directions of research activity of students are defined as Humanities, natural Sciences, engineering, computer science and programming. The organizational and psychological-pedagogical conditions to ensure the effectiveness of scientific-research work of students are grounded. The expediency of the multistage forms of organization of research activity of students is defined, and the essential characteristics of each stage are disclosed. The phased development identified in the research competencies with specific professional training of students in technical universities is emphasized. Scientific knowledge is the backbone beginning in technical research, exerting a significant influence on the quality of graduates. The work also reveals the humanistic orientation of the research work of students.